Pengaruh Terpaan Program Buser Investigasi SCTV “Tempe Kardus Berbalut Kertas” Terhadap Kecemasan Masyarakat Kota Pematangsiantar - Andini Rahmadia Nasution; Faizal Hamzah Lubis (Universitas Muhammadiyah Sumatera Utara, 2022)
Mass media plays an important role in delivering messages and information to the public. Television media is the most trusted media source to get information. Crime news has high stimulation for its viewers because safety ranks first for basic human needs. The investigation buser program is a criminal news program that is presented in more depth. It is undeniable that television media can influence people's attitudes, behavior, and perceptions, one of which is anxiety. Anxiety is one of the natural reactions that arise in humans. This study aims to determine the effect of exposure to the SCTV investigation buser program